Bank card service quality at Techcombank - Nguyen, Anh Tu (Khoa Quốc tế, ĐHQGHN, 2020)
The survey results show that Responsiveness has the strongest impact on bank card service quality at Techcombank, then Tangibles, Reliability, Assurance and Empathy respectively. The bank has some achievements in providing bank card service to customers, such as procedures for bank card transactions are strictly followed by banking employees, the bank does well in information confidentiality and transparency for customer information and banking transactions, etc. However, sometimes bank card services are not provided to customers as quickly as possible, errors in the bank card system also may cause delay in providing services to customers, sometimes banking officials at Techcombank do not have very polite and professional working attitudes and behaviors, causing customers to have negative ideas about the bank’s working style, etc. The author also gave out some solutions to improve bank card service quality at Techcombank including reducing job stress and pressure for banking employees, reducing errors in the banking system, improving banking expertise and skills necessary for banking employees, effectively motivating banking employees, making more suitable job allocation, and paying attention to recruitment and selection works of the bank.